Advances in Nanomedicine for Targeted Drug Delivery Systems - Hidayat, Rahmat (Magenta Journal De Healthymedi, 2024)
Advancements in nanomedicine have revolutionized drug delivery systems, enabling targeted therapies that enhance drug efficacy and reduce systemic toxicity. This review explores recent developments in nanoparticle-based drug delivery systems, focusing on various types of nanoparticles, including liposomes, polymeric nanoparticles, dendrimers, and stimuli-responsive systems. The mechanisms of targeted drug delivery, including passive and active targeting strategies, are discussed, highlighting the role of the enhanced permeability and retention (EPR) effect. Clinical applications, particularly in oncology and neurodegenerative diseases, are examined, showcasing the potential of these systems to improve patient outcomes. Despite the promising advances, challenges such as safety, scalability, and regulatory hurdles remain significant obstacles to the widespread clinical adoption of nanoparticle-based therapies. Future directions emphasize the integration of nanomedicine with emerging technologies and personalized medicine, paving the way for innovative therapeutic solutions.